Análise de desempenho de um fogão solar com parabola fabricada em material compósito - Macedo Neto, Miguel Cabral de (2011)
It is presented a solar cooker made with a parabolic reflector composed by a composite material. For this purpose, it was utilized a cast concrete with a parabolic profile obtained by means of modeling. It will be demonstrated the manufacturing process and settings, as well as tests results, in order to determine the contact temperature and cooking time of some foods. This solar cooker presents the following main characteristics: the concentration method, low cost and easy manufacturing process. It was performed by employing recycled materials such as cement, plaster, crushed polystyrene and wheels. The captation area measures 1 square meter and its parabole was covered with a mirrors measuring 25 cm2. A temperature higher than 650°C was obtained. Furthermore, it has been demonstrated that the cooking viability for several type of foods such as beans, potatoes, rice, yams and pasta can be used in two meals for a family of four. In addition, the advantages of this cooker were analysed in comparison with others described in literature as well as those operating on gas. Especially in Northeast of Brazil, where there is a potential for solar energy, this prototype is an important tool, because it avoids not only desertification, but also pollutants from burning firewoods which cause ecological imbalance